Speech Act Analysis of English Teacher Talk at SMP Negeri 1 Rangkasbitung - Siti Hanna Sumedi; Dery Rovino (Universitas Bunda Mulia, 2020)
Teachers’ talk is a factor that may entail to the smoothness of English teaching and learning experience. Besides, language used by teacher in the classroom is crucial, because it will influence students’ learning process and development. This study investigated the speech acts in the teacher talk at SMP Negeri 1 Rangkasbitung. This study involved the Seventh Grade English teacher of SMP Negeri 1 Rangkasbitung as the data source. Furthermore, this study used Searle’s theory of speech acts classification as the instrument for analyzing the data. Based on the analysis, there were only four types of speech acts found in the teacher talk, 68 % directive speech act, assertive speech acts with 14 %, and the last two of speech act, commissive and expressive speech act, were only 10 % and 8 % in the teacher talk during the teaching-learning process. This study revealed that the majority of teacher talks found in the form of directive speech act, in the other words the classroom interaction went one way which more likely teacher-centeredness. Likewise, the teacher-centeredness make the students talk less and most importantly make the students became dependent and passive learner. In this study, the teacher became the central subject of learning rather than the students, hence it goes against the demands of National Standard and did not follow the principles of current Indonesian curriculum. Therefore, the conclusion which can be drawn from this study is that the teacher should utilize speech acts appropriately because high quality and the appropriateness of the teacher’s speech acts can convey teaching materials effectively, enhance teaching efficiency easily, and provide active learning meaningfully.